Intellectual and Technological Development of Regions: Challenges and Ways to Address them - Bochko, Vladimir Stepanovich (Economy of Regions, 2017)
The article reveals the issues of intellectual and technological development of the country and regions. The author shows that growing number of employees with higher education is not accompanied by a proportionate increase in the technology level of the economy. This is due to the change of the purpose of higher education. Gradually, the higher education has become a tool ensuring a common cultural level of the population. The author analyses major reasons for a weak contribution of an increasing number of employees with higher education to the technological growth. Professional researchers and employees from various types of industries should be considered as producers of intellectual and technological development. I suggest calling them the generators of intelligent technologies. The authors interpretation of the concept of «scientific and research education» implies not only the development of creative abilities, but also the understanding of the causes and consequences of natural and social processes as well as critical reflection on these processes. Scientific and research education is emerging directly from research activity. The support of scientific and research education keeps in the society the desire of scientific breakthroughs. The author has revealed the negative tendencies in science. They are related to a considerable decrease in research and development as well as to the withdrawal of the Russian business from the sphere of scientific research. I conclude that there is an urgent need to invest into science. This will result in scientific and technological progress, which would develop the society and increase the productivity of social activities.